IMPLEMENTASI AMAR MA'RUF NAHI MUNGKAR DALAM KEHIDUPAN SOSIAL - Kartini; Fachrur Rizha (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
The command for every Muslim to convey to each other is good and prevent evil. In addition to carrying out the commands of Allah and His Messenger, Amar ma'ruf nahi munkar can also maintain a better order of social life and community environment. Indifference to the munkar will invite the punishment of Allah which will not only be felt by the perpetrators of the munkar, but also by the entire community in the munkar environment. As happened to the previous people and has been enshrined in the Qur'an. In da'wah to prevent evil, a preacher must understand the mad'u he is facing and always be advised to prioritize a gentle way of delivering da'wah, although sometimes he must apply firmly under certain conditions. Believers are likened to one body, and to keep it good, it is necessary to maintain an attitude of mutual care and invite to good and prevent evil. The implementation of amar'maruf nahi munkar can not only be done verbally but can also be done in writing.